Stromatolites and pulsed oxygenation events in the Mesoproterozoic Longjiayuan formation of western Henan: evidence for life-environment co-evolution - Qianqian Li; Deshun Zheng; Fengbo Sun (Scientific Reports)
Abstract The oxygen level in the ocean and atmosphere played a crucial role in the development of Precambrian stromatolites. The Mesoproterozoic represents a critical interval in Earth’s history, characterized by persistently low atmospheric and oceanic oxygen levels under which stromatolites flourished. Stromatolites are particularly abundant in Member II of the Mesoproterozoic Longjiayuan formation in western Henan Province. To investigate the relationship between stromatolites and redox conditions, petrographic and geochemical analyses were conducted on siliceous-banded dolomites and stromatolitic dolomites from the Longjiayuan Formation. The results show that the macromorphology of stromatolites in Member II is classified into stratiform, undulatory, domical, conical, and columnar morphologies. Microscopically, the stromatolites exhibit alternating light and dark laminae, with occasional ooids and spherules. The CeSN/CeSN* values recorded in carbonate rocks from Member II show negative anomalies, reflecting oxidizing conditions influenced by environmental changes and microbial activity. These stromatolite records and oxygen fluctuations in the Mesoproterozoic shallow marine environment provide a valuable basis for studying the co-evolution of early life and the environment.